2017
DOI: 10.1111/rssc.12230
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spatial Data with a Nested Correlation Structure

Abstract: Summary Spatial statistical analyses are often used to study the link between environmental factors and the incidence of diseases. In modelling spatial data, the existence of spatial correlation between observations must be considered. However, in many situations, the exact form of the spatial correlation is unknown. This paper studies environmental factors that might influence the incidence of malaria in Afghanistan. We assume that spatial correlation may be induced by multiple latent sources. Our method is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 79 publications
(131 reference statements)
1
23
0
Order By: Relevance
“…Descriptive summaries of study characteristics were presented as mean, median and interquartile range. Often in spatial data, there is some degree of dependency among observations within a geographical space (28,29); therefore, we measured the bivariate spatial autocorrelation between county-level health factors and the number of confirmed COVID-19 cases using Moran's Index based on Queen's contiguity spatial-lag of order 1 (immediate neighbors) (30). Moran's I is the most common measure of global spatial autocorrelation which gives the overall distribution of departures from randomness.…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive summaries of study characteristics were presented as mean, median and interquartile range. Often in spatial data, there is some degree of dependency among observations within a geographical space (28,29); therefore, we measured the bivariate spatial autocorrelation between county-level health factors and the number of confirmed COVID-19 cases using Moran's Index based on Queen's contiguity spatial-lag of order 1 (immediate neighbors) (30). Moran's I is the most common measure of global spatial autocorrelation which gives the overall distribution of departures from randomness.…”
Section: Discussionmentioning
confidence: 99%
“…While the work of Rivers and colleagues was practically impeccable, their analysis adopted Poisson regression models using a robust variance estimator without accounting for area-specific geographical effects to capture extra variation in the model. Ignoring spatial pattern in infectious disease may be inadequate to explain the variation in the occurrence of the disease due to space as it has been found that most diseases are location related [ 41 , 42 ]. Similarly, Alraddadi et al, [ 14 ] considered only primary MERS-CoV cases reported in Saudi Arabia during March–November 2014 in their study.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a number of applications of statistical models for prediction of infection rates and spread during the COVID-19 pandemic [9,10]. However, mapping of disease incidence to identify spatial clustering and patterns remains an important pathway to understanding disease epidemiology and is required for effective planning, prevention or containment action [11][12][13]. There are a few studies that attempt to map the pandemic in China [14] and in Iran [15].…”
Section: Introductionmentioning
confidence: 99%